2020
DOI: 10.1021/acs.est.9b05184
|View full text |Cite
|
Sign up to set email alerts
|

Total Bioaerosol Detection by a Succinimidyl-Ester-Functionalized Plasmonic Biosensor To Reveal Different Characteristics at Three Locations in Switzerland

Abstract: Bioaerosols consisting of biologically originated airborne particles such as microbes, metabolites, toxins, and fragments of microorganisms are present ubiquitously in our living environment. The international interests in bioaerosols have rapidly increased because of their many potential health effects. Thus, accurate and fast detection of total bioaerosols in different environments has become an important task for safeguarding against biological threats and broadening the pool of bioaerosol knowledge. To qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Thus, based on the LSPR signal−target size relationship, the estimated LoD for detecting the entire RNA strands from SARS-CoV-2 could be approximately 2.26 × 10 4 copies. 38 A recent study reported the viral loads of SARS-CoV-2 from different respiratory trace samples including the throat/nasal swabs and the sputum. Based on these clinical specimens collected from 82 infected individuals, the overall viral load soon after onset was higher than 1 × 10 6 copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, based on the LSPR signal−target size relationship, the estimated LoD for detecting the entire RNA strands from SARS-CoV-2 could be approximately 2.26 × 10 4 copies. 38 A recent study reported the viral loads of SARS-CoV-2 from different respiratory trace samples including the throat/nasal swabs and the sputum. Based on these clinical specimens collected from 82 infected individuals, the overall viral load soon after onset was higher than 1 × 10 6 copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to optical components, functional photonic nanostructures have also been incorporated within optofluidic devices for the signal transduction in biochemical sensing. For example, Qiu et al and Funari et al coated the glass substrate with gold islands by dewetting [52][53][54] and gold nanospikes by electrodeposition [55], respectively. The glass slides were then bounded with Teflon or PDMS microfluidics, while the gold islands and nanospikes were further functionalized for localized surface plasmon resonance (LSPR)based biosensing.…”
Section: Signal Transductionmentioning
confidence: 99%
“…[91] The nanostructured end-face was inserted into a microfluidic channel for real-time biosensing and the reported limit of detection was found to be 0.1 pg/mL. Qiu et al proposed a strategy for the measurement of total bioaerosol-based LSPR [53], as shown in Figure 9b. The gold nanoislands were functionalized with succinimidyl ester, which can detect the bioaerosols by chemically reacting with the amine group.…”
Section: Plasmonic Based Optofluidic Biosensingmentioning
confidence: 99%
“…These "half" antibodies can be directly covalent immobilized to the gold surface, taking advantage of the thiol groups simplifying the creation of the biointerfaces, and enhancing the biodetection sensitivity by decreasing the biorecognition events thickness. In environmental analysis, Qiu et al (2020) have recently demonstrated the detection of total bioaerosols from real samples obtained in different locations around Switzerland. Bioaerosols are a complex mixture of viruses, toxins, and allergens, with a relevant influence on human health.…”
Section: Bioanalytical Applicationsmentioning
confidence: 99%